Internalisasi Ajaran Yoga dalam Pendidikan Karakter Anak Usia Dini - Putu Emy Suryanti; Kadek Bayu Indrayasa (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
The development of science and information and also technology has a big impact on human life. Not only positive impacts that make it easier for humans in everything, but also negative impacts, one of which is the moral degradation of the childrens. This moral degradation can cause problems in various aspects of life. To overcome the problem of moral degradation, the government has launched character education at every level of education, including early childhood education. Early childhood is experiencing rapid growth and development, so that this age is very decisive in shaping the character and personality of children. Therefore, children need to be trained to form good character. One of the activities that children can do to support growth and development, including shaping children's character, is yoga. Yoga as an activity of body work, breathing, and mind work is an activity with various benefits. In addition to getting physical and psychological health from practicing yoga, children can also learn the noble values that exist in the teachings of yoga for the formation and development of children's character as early as possible.Keywords: yoga, character education, early childhood.